
3个回答
展开全部
a2+2ab+b2=0
(a+b)^2=0
a=-b
a(a+4b)-(a+2b)(a-2b)=(-b)(3b)-b(-3b)=-3b^2+3b^2=0
(a+b)^2=0
a=-b
a(a+4b)-(a+2b)(a-2b)=(-b)(3b)-b(-3b)=-3b^2+3b^2=0
展开全部
a(a+4b)-(a+2b)(a-2b)=a^2+4ab-(a^2-4b^2)=4ab+4b^2
因a^2+2ab+b^2=0,即 (a+b)^2=0,即a+b=0
则原式为4b(a+b)=0
因a^2+2ab+b^2=0,即 (a+b)^2=0,即a+b=0
则原式为4b(a+b)=0
已赞过
已踩过<
评论
收起
你对这个回答的评价是?
展开全部
解:a(a+4b)-(a+2b)(a-2b)=a^2+4ab-(a^2-4b^2)=4ab+4b^2
因为a^2+2ab+b^2=0,
即(a+b)^2=0,即a+b=0
所以原式为4b(a+b)=0
因为a^2+2ab+b^2=0,
即(a+b)^2=0,即a+b=0
所以原式为4b(a+b)=0
已赞过
已踩过<
评论
收起
你对这个回答的评价是?
推荐律师服务:
若未解决您的问题,请您详细描述您的问题,通过百度律临进行免费专业咨询